Novel Solutions to Student Problems: A Phenomenological Exploration of a Single Session Approach to Art Therapy With Creative Arts University Students - Wilson, Elizabeth (Frontiers in Psychology, 2021)
Within the Australia university context, research has uncovered increasing levels of psychological distress, in the form of stress, anxiety and depression (O’Keeffe, 2013). Higher rates of psychological distress have been reported amongst undergraduate students specifically enrolled in creative arts programs (Baik, Larcombe, et.al., 2018). Despite these increasing levels of psychological distress, university students are reluctant to engage with mental health and wellbeing supports (Burns, Birrell, 2014). To explore ways to meet the mental health and wellbeing needs of creative arts university students, the Creative Arts and Music Therapy Research Unit (CAMTRU) at The University of Melbourne commenced a project exploring the benefits and pitfalls of a brief creative arts therapies approach for students attending a campus based wellbeing clinic. This exploratory research study formed the art therapy component of this much broader research endeavour. Creative arts students in this research study were invited to participate in a single session art therapy (SSAT) encounter that involved the visual exploration of the miracle question that asked students to visually depict “what the problem looks like and how it will look when the problem is resolved or you feel like you can cope with it better?” (Riley, 1999). Descriptive findings of this exploratory research study, revealed how the combination of art therapy used within a single session framework, afforded students a novel means to externalize problems, leading students to forming a less internalized view of the self.